Risk Mapping of Tsunami Ambulu Sub-District, Jember Regency - Adden Ramadhan Syarif Ardi; Gusfan Halik; Retno Utami Agung wiyono (Fakultas Teknik, Universitas Brawijaya, 2023)
Tsunami risk level mapping was carried out in Ambulu Sub-District, Jember Regency, to determine the tsunami risk level in the area. Tsunami risk mapping was carried out by including several components such as vulnerability, which consists of several assessment aspects by the Chief of the National Disaster Management Agency Regulation of the Year 2012, and capacity, which is weighted according to the Chief of the National Disaster Management Agency Regulation of the Year 2012. The hazard component was generated from the bathtub method. The tsunami risk level was obtained after overlaying using a GIS application (Geographic Information System). A very high level of risk is found to apply for Sumberejo Village, with an area of 286 Ha, and Sabrang Village, with an area of 288 Ha. Villages at very high risk are directly adjacent to the coast and have high vulnerability and low disaster management capacity. The other villages, such as Karanganyar Village, Ambulu Village, Tegalsari Village, Andongsari Village, and Pontang Village, do not have a very high tsunami risk because they are far from the coastline and have low vulnerability and high disaster response capacity.